Effect of Temperature on Biological Character of Spodoptera frugiperda J.E. Smith - Ramadhan, R. Arif Malik; Isnaeni, Selvy (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2024)
Spodoptera frugiperda is a pest that is capable of migrating over a wide range. Currently, the S. frugiperda attack can be said to be comprehensive in almost all regions of Indonesia. The level of adaptability of S. frugiperda to the suitability of the agroecosystem needs to be reviewed further in order to predict the potential for S. frugiperda attacks in the future. This research aims to test the suitability of temperature for the biological activity of S. frugiperda. The treatments tested in this study included temperatures (A) 34.0±2.2 oC, (B) 27.0±4.1 oC, and (C) 19.0±1.3 oC. Each treatment used 5 larvaes 2nd instar and was repeated 6 times so that the number of test insects used was 120. The parameters observed in this study included growth, development, feeding activity and mortality rate of the test insects. The data obtained was then analyzed using ANOVA and tested further with DMRT at an error level of 5%. Differences in rearing temperature can affect growth, development, feed consumption and larval mortality. Temperature (B) 27±4.1 ℃ is the most suitable temperature for S. frugiperda. Temperatures (A) 34.0±2.2 ℃ and (C) 19.0±1.3 ℃ are less suitable temperatures, but S. frugiperda can still carry out its life cycle. This research can provide an overview to anticipate S. frugiperda attacks that may occur due to global warming in the future.